Direct Pulp-Capping with Calcium Enriched Mixture in Primary Molar Teeth: A Randomized Clinical Trial - Fallahinejad Ghajari, Masoud; Asgharian Jeddi, Tahereh; Iri, Sonay; Asgary, Saeed (Iranian Endodontic Journal, 2010)
INTRODUCTION: The aim of this trial was to compare clinical and radiographic success rates of direct pulp capping (DPC) using a novel biomaterial called Calcium Enriched Mixture (CEM) cement versus Mineral Trioxide Aggregate (MTA) in primary molar teeth. MATERIALS AND METHODS: In this randomized clinical trial 42 deciduous molars in 21 patients who had at least two teeth requiring DPC, were treated. The enrolled patients were between 5-8 years. The molar teeth were randomly divided into two experimental groups. Patients and operators were blinded. The teeth were anaesthetized, caries were removed and after pinpoint exposure of dental pulp, haemostasis was achieved. The exposure points were capped with MTA or CEM cement. All teeth were restored with amalgam. Patients were recalled for the 6-month follow up. Statistical analysis was carried out using McNemar test. RESULTS: Thirty-eight teeth were available for follow up (19 in each group). The radiographic evaluations did not show failure in experimental groups; however, in clinical examinations one sinus tract was found in CEM cement group. Clinical success rates in CEM cement and MTA groups were 94.8% and 100%, respectively. Dentinal bridge formation was not observed in the two experimental groups. CONCLUSION: There is no significant difference between treatment outcomes of direct pulp capping with either CEM cement or MTA; therefore, both biomaterials can be used successfully for DPC in primary molar teeth.